Bi‐level Programing Merger Evaluation and Application to Banking Operations. Issue 3 (21st March 2014) - Wu, Desheng Dash; Luo, Cuicui; Wang, Haofei; Birge, John R.
Abstract : The potential for operational efficiency improvement is a key consideration for firms contemplating the consolidation of both internal and external business units. This paper develops a leader–follower game model to assess such potential gains from the merger of different organizations with constrained resources. A profit‐sharing strategy and algorithm are proposed to solve the model while maintaining incentive compatibility within each unit's decision‐making process. This paper further demonstrates that in a framework, within the data envelopment analysis paradigm, a supply chain with an upstream leader and downstream followers is efficient if and only if both the leader and the followers are individually efficient. A case study of a banking operations merger shows how incentive compatible merger of operations can produce overall efficiency improvement.